Approaches to the Management of Hypertension in Resource-Limited Settings: Strategies to Overcome the Hypertension Crisis in the Post-COVID Era - Skeete, Jamario (Integr Blood Press Control, 2020)
The COVID-19 pandemic has changed most aspects of everyday life in both the non-medical and medical settings. In the medical world, the pandemic has altered how healthcare is delivered and has necessitated an aggressive and new coordinated public health approach to limit its spread and reduce its disease burden and socioeconomic impact. This pandemic has resulted in a staggering morbidity and mortality and massive economic and physical hardships. Meanwhile, non-communicable diseases such as hypertension, diabetes mellitus, and cardiovascular disease in general continue to cause significant disease burden globally in the background. Though presently receiving less attention in the public eye than the COVID-19 pandemic, the hypertension crisis cannot be separated from the minds of healthcare providers, policymakers and the general public, as it continues to wreak havoc, particularly in vulnerable populations in resource limited settings. On this background, many of the strategies being employed to combat the COVID-19 pandemic can be used to re-energize and galvanize the fight against hypertension and hopefully bring the public health crisis associated with uncontrolled hypertension to an end.